Integrated Plans of City Development as a Tool of Local Development, on the Example of Ústí Nad Labem - Koutský, Jaroslav (Zintegrowane plany rozwoju miasta jako narzędzie rozwoju lokalnego, na przykładzie Ústí nad Labem, 2010)
The text deals with the problem of Integrated Plans (IPCD) of city development. There is a discussion of their contribution to the city development. The main aim of IPCD is to coordinate activities and to concentrate sources for solving the most serious identified problems and for using economic and further development potential of cities. The case study is elaborated for Usti nad Labem city (The Czech Republic) which in long-term horizon faces significant development problems that are primarily caused by negative heritage of the state which was shaped before 1989. Nowadays the city has new experience within the implementation of integrated plan of city development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 109, s. 52-57